Visceral varicella zoster virus infection after allogeneic stem cell transplantation. Issue 3 (1st April 2013) - Doki, N.; Miyawaki, S.; Tanaka, M.; Kudo, D.; Wake, A.; Oshima, K.; Fujita, H.; Uehara, T.; Hyo, R.; Mori, T.; Takahashi, S.; Okamoto, S.; et al.
Abstract Introduction Varicella zoster virus (VZV) disease is one of the major infectious complications that can occur after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Many reports have shown visceral VZV infection, a special type of VZV disease, to be rare. However, few studies so far have included a large number of patients. Findings Visceral VZV infection was found in 20 (0.8%) of 2411 patients who underwent allo‐HSCT at our hospitals. Seventeen (85%) patients were taking immunosuppressive agents at the time of presentation with zoster. The presenting symptom was abdominal pain in 16 patients (80%), unconsciousness in 3 patients (15%), and no symptoms in 1 patient. The mean time interval from allo‐HSCT to symptomatic visceral VZV infection was 273 days (103–800 days). The eruptions appeared within 3 days (0–13) after the first symptoms. Treatment with intravenous acyclovir was initiated before the appearance of eruptions in 3 of 18 patients (all 3 survived) with vesicular eruptions, the same day in 12 patients (11 survived, 1 died), and after the appearance in 3 patients (1 survived, 2 died). The overall mortality was 20%. Conclusion In conclusion, these data confirm that the incidence of visceral VZV infection is infrequent, but this disease is serious. When patients being treated with immunosuppressive agents demonstrate abdominal pain or unconsciousness, the possibility of visceral VZV infection should be considered as well as earlier therapeutic intervention.